Overview on Monitoring of Therapeutic Drugs - Gawade, Shivaji Prataprao (Indian Journal of Pharmacy Practice)
Purpose: The drug monitoring services are to obtain clinical pharmacokinetic data that results into fewer adverse reactions, shorter intensive care and shortened overall period of hospitalization. The monitoring of plasma level of therapeutic drugs can help to distinguish between noncompliant and a true non responder patient and to individualize dosage regimen in a particular disease state. Methods: The drug monitoring measurements involve interpretation of number of variables such as date, time, route of administration, clinical state of patient. Methods include, three components structural, process and output measurement, three types of drug monitoring, clinical, biochemical and plasma drug concentration measurements; analytical methods for quantification and modern highly sensitive methods used for concentration measurement from micro volume samples. Conclusion: The monitoring of therapeutic drugs is especially for personalizing medicine in ageing population and to optimize the efficacy of drugs in children as there are differences in absorption, disposition and pharmacological effects of most drugs between adult and children. The present overview, exemplifies various parameters influencing drug monitoring, priori and posteriori drug monitoring, limitations and applications of drug monitoring.
Keywords: Therapeutic range; Priori; Posteriori; Sampling; Monitoring